2022
DOI: 10.3390/nu15010159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Diversity on Growth Outcomes of Children Aged 6 to 23 Months in India: Evidence from National Family and Health Survey

Abstract: Low dietary diversity significantly interplays with children’s growth failure. However, evidence of its crucial role in children’s health remains inconclusive in developing countries such as India. This study attempts to find the association between dietary diversity and growth outcomes among children aged between 6 and 23 months in India using the fourth round of the National Family Health Survey (NFHS), 2015–2016. A total of 67,278 mother-child pairs of children between the ages of 6–23 months and mothers ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…A less diverse dietary pattern indicates poor food quality, leading to suboptimal growth in stunted children due to deficiencies in individual nutrients or a combination of several nutrients. This is consistent with research conducted in India by Saha et al (2023) it is reported that a significantly varied dietary pattern is associated with a decrease in stunting, and the risk of stunting decreases significantly as the number of food groups consumed increases. Therefore, the analysis of food diversity score and minimum dietary diversity (MMD) indicates that children who consume a varied or diverse diet are less likely to experience nutritional deficiencies compared to children with less varied dietary patterns.…”
Section: Resultssupporting
confidence: 92%
“…A less diverse dietary pattern indicates poor food quality, leading to suboptimal growth in stunted children due to deficiencies in individual nutrients or a combination of several nutrients. This is consistent with research conducted in India by Saha et al (2023) it is reported that a significantly varied dietary pattern is associated with a decrease in stunting, and the risk of stunting decreases significantly as the number of food groups consumed increases. Therefore, the analysis of food diversity score and minimum dietary diversity (MMD) indicates that children who consume a varied or diverse diet are less likely to experience nutritional deficiencies compared to children with less varied dietary patterns.…”
Section: Resultssupporting
confidence: 92%
“…In this regard, a diversified diet after the sixth month is crucial as exclusive breastfeeding is no longer sufficient to meet the nutritional needs of growing children. Another study also confirmed that insufficient intake of dietary diversity has a direct impact on children’s growth outcomes, manifested as weight loss and underweight, as well as corresponding severe forms ( 36 ). Children who consume sufficient animal derived foods (such as dairy products, meat, and eggs) are least likely to experience developmental delays, weight loss, and underweight.…”
Section: Discussionmentioning
confidence: 66%
“…It is also recommended by researchers to readdress and promote and make animal-source proteins available to vulnerable groups and low-income countries. Dietary diversity plays a crucial role to promoting linear growth, where animal-source proteins such as meat, fish, seafood, egg, milk, and dairy products are necessary for ensuring minimum dietary diversity (MDD) [35]. The indispensable amino acid (IAA) bioavailability and possible postprandial plasma IAA concentrations of animal-source proteins are likewise significantly higher than those of plant-source proteins.…”
Section: Discussionmentioning
confidence: 99%